Molecular networks involved in mouse cerebral corticogenesis and spatio-temporal regulation of Sox4 and Sox11 novel antisense transcripts revealed by transcriptome profiling. - Ling, King Hwa; Hewitt, Chelsee Ann; Beissbarth, Tim; Hyde, Lavinia; Banerjee, Kakoli; Cheah , Pike See; Cannon, Ping Z.; Hahn, Christopher N.; Thomas, Paul Q.; Smyth, Gordon K.; Tan, Seong-Seng; Thomas, Tim; et al. (BioMed Central, 2009)
Background: Development of the cerebral cortex requires highly specific spatio-temporal regulation of gene expression. It is proposed that transcriptome profiling of the cerebral cortex at various developmental time points or regions will reveal candidate genes and associated molecular pathways involved in cerebral corticogenesis.